Mask off, game on!: strengthening our anaesthesia family 2025 - Ahmad Hisham, Nurafza; Ahmad, Fauziah (Faculty of Medicine, 2025)
On 9 August 2025, the Department of Anaesthesia and Intensive Care UiTM successfully organised its inaugural Team Building event at Beacon Resort, Kerling, Selangor. Set amidst tranquil rivers, natural hot springs, and lush greenery, the programme aimed to strengthen bonds, promote wellbeing, and revitalise team spirit among departmental members and their families.